Neonatal and maternal outcome in term primigravida with isolated oligohydramnios - Agarwal, Shelly; Gupta, Samta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The aim of this study is to evaluate the maternal and perinatal outcome in term primigravida with isolated oligohydramnios. Methods: A retrospective, case–control study was carried out in the department of OBG, School of Medical Sciences and Research, Sharda Hospital, Greater Noida from November 2014 to October 2017. The study population comprised of low-risk primigravida with singleton, term pregnancy, with vertex presentation and intact membranes. After meeting the inclusion and exclusion criterion, the study population was divided into cases (n = 51) and control group (176) and the results were analyzed in reference to rate of induction of labour, C. Section rate and the perinatal outcome. Results: Isolated oligohydramnios is associated with increased rate of induction of labour and increased operative interference, but perinatal outcome in terms of mean birth weight, Apgar score at 5 min and NICU admissions for over 24 hours, are not statistically significant in comparison with control group. Conclusions: Isolated oligohydramnios is not an indicator of adverse perinatal outcome.